2019
DOI: 10.3390/v11060503
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Feline Leukaemia Virus (FeLV) Infection in Owned and Group-Housed Rescue Cats in Australia

Abstract: A field study was undertaken to (i) measure the prevalence of feline leukaemia virus (FeLV) exposure and FeLV infection in a cross-section of healthy Australian pet cats; and (ii) investigate the outcomes following natural FeLV exposure in two Australian rescue facilities. Group 1 (n = 440) consisted of healthy client-owned cats with outdoor access, predominantly from eastern Australia. Groups 2 (n = 38) and 3 (n = 51) consisted of a mixture of healthy and sick cats, group-housed in two separate rescue facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 49 publications
1
41
1
1
Order By: Relevance
“…14 In a study of 440 owned pet cats in Australia, 11% were classified as having presumptively abortive infection, 2% as presumptively regressive and 0.5% as presumptively progressive. 15 This suggests that abortive infection may be the most common outcome following exposure under typical conditions. In contrast, in two populations of cats in Australia (one group of 38 cats and one group of 51 cats) in which FeLV-infected and uninfected cats were co-mingled without separating healthy from clinically ill cats, 9% were classified as having abortive infection, 25% as regressive and 21% as progressive, suggesting that resistance to infection may be compromised by intense infectious pressure, comorbidities and a stressful environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In a study of 440 owned pet cats in Australia, 11% were classified as having presumptively abortive infection, 2% as presumptively regressive and 0.5% as presumptively progressive. 15 This suggests that abortive infection may be the most common outcome following exposure under typical conditions. In contrast, in two populations of cats in Australia (one group of 38 cats and one group of 51 cats) in which FeLV-infected and uninfected cats were co-mingled without separating healthy from clinically ill cats, 9% were classified as having abortive infection, 25% as regressive and 21% as progressive, suggesting that resistance to infection may be compromised by intense infectious pressure, comorbidities and a stressful environment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in two populations of cats in Australia (one group of 38 cats and one group of 51 cats) in which FeLV-infected and uninfected cats were co-mingled without separating healthy from clinically ill cats, 9% were classified as having abortive infection, 25% as regressive and 21% as progressive, suggesting that resistance to infection may be compromised by intense infectious pressure, comorbidities and a stressful environment. 15 Viral RNA is usually detectable in plasma by real-time reverse-transcriptase polymerase chain reaction (qRT-PCR) testing within 1 week of FeLV exposure, followed by pro viral dNA detection by PCR within 2 weeks of exposure and finally by FeLV antigen detection, which usually occurs by 30 days but can be longer in some cats. 16 It is not only cats with progressive infection that undergo the early phases, but also some cats with regressive infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Several studies have since confirmed the presence of regressively FeLV-infected cats (ie, provirus-positive, free p27 antigen-negative) in different cat populations worldwide. 16,38,62,75 Provirus PCR on blood produces positive test results sooner after FeLV exposure than p27 antigen detection ( Table 2). In experimental studies, cats were provirus-positive 1-2 weeks after FeLV exposure (vs 3-6 weeks for p27 antigen).…”
Section: Provirus Carriersmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that FeLV test results can revert from positive to negative status, potentially signaling a regressive or abortive infection. 1,[8][9][10] Even when using high-accuracy tests, the complex natural history of FeLV infection makes it difficult to secure a definitive diagnosis, which presents an added challenge to the identification and effective management of FeLV-infected shelter cats. 10,11 Regressive infections are associated with a robust immune response that may, at times, suppress viral loads below the level of detection following an initial period of transient antigenemia.…”
Section: Introductionmentioning
confidence: 99%